1991
DOI: 10.1007/bf00233859
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar muscularity and its relationship with age, occupation and low back pain

Abstract: This paper considers an internal standard of lumbar muscularity. The cross-sectional areas (Acs) of the intervertebral disc and paraspinal muscles were measured in 147 working men from an axial magnetic resonance image passing through the L3-4 disc. Lumbar muscularity was expressed by two ratios; the ratio between the Acs of the right psoas and the Acs of the intervertebral disc (P:disc), and the ratio between the combined Acs values of the right erector spinae and quadratus lumborum and the Acs of the disc (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Previously this information had been obtained from cadaveric studies [3,22] and computed tomography [23]. More recently, MRI has been used to gather such information [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previously this information had been obtained from cadaveric studies [3,22] and computed tomography [23]. More recently, MRI has been used to gather such information [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, increased back strength is not necessarily associated with the prevention of LBP. Some studies have reported no advantage of trunk strengthening (33) or lumbar muscularity (41) in the prevention of LBP. Yet, increased back strength may provide some protection from LBP when greater forces are needed for the task (11).…”
Section: Trunk Strengthening With Instability Resistance Exercisesmentioning
confidence: 99%
“…Muscle PCSA was changed based on coefficient of variation of muscle cross-sectional area (CSA) in four studies ( Savage et al, 1991 ; Frantz Pressler et al, 2006 ; Kamaz et al, 2007 ; Fortin et al, 2015 ). From ( Frantz Pressler et al, 2006 ), the average of all participants was used, and average coefficient of variation of left and right muscle was calculated (0.14).…”
Section: Methodsmentioning
confidence: 99%